1986
DOI: 10.1128/jb.166.2.565-573.1986
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of livH, the structural gene encoding a component of the leucine transport system in Escherichia coli

Abstract: The physical location of the genetically defined livH gene was mapped in the 17-kilobase plasmid pOX1 by using transposon Tn5 inactivation mapping and further confirmed by subcloning and complementation analysis. These results indicated that the livH gene maps 3' to livK, the gene encoding the leucine-specific binding protein. Moreover, the nucleotide sequence of the livH gene and its flanking regions was determined. The livH gene is encoded starting 47 base pairs downstream from the livK gene, and it is trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…This revealed a clear difference in the rate of degradation of the transcripts ( mRNA degradation (1, 3, 4, 12, 13, 21). Differential expression is especially prevalent when one or more of the gene products is an integral membrane protein (2,8,10,20), as is the case with arsB (26). The molecular mechanism responsible for the decreased expression of these proteins is obscure.…”
Section: Methodsmentioning
confidence: 99%
“…This revealed a clear difference in the rate of degradation of the transcripts ( mRNA degradation (1, 3, 4, 12, 13, 21). Differential expression is especially prevalent when one or more of the gene products is an integral membrane protein (2,8,10,20), as is the case with arsB (26). The molecular mechanism responsible for the decreased expression of these proteins is obscure.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies involving purified BPs showed that LIV-BP, encoded by the livJ gene, binds isoleucine, leucine, and valine with K d values of 10 Ϫ6 to 10 Ϫ7 M and threonine, serine, and alanine with lower affinity and that LS-BP, encoded by the livK gene, binds leucine with a K d value of approximately 10 Ϫ6 M (24). To enable the ATP-hydrolysis-coupled transport of their substrates into the cytoplasm, LIV-BP and LS-BP interact with the common inner-membrane components LivHMGF, which constitute the LIV-I and LS systems, respectively (1,28,29,45,50). These six liv genes are clustered at 77 min on the chromosome (45) and divided into two transcription units, one for livJ and the other for livKHMGF (1,18,45).…”
Section: Vol 186 2004mentioning
confidence: 99%
“…The brnQ gene product, BrnQ protein, is very hydrophobic, similar to that found in the LivH protein, which is a membrane-bound component of the LIV-I system in Escherichia coli (Nazos et al, 1986). The BrnQ protein contains several hydrophobic segments consisting of an average of 30 amino acid residues, which may span the cell membrane (Fig.…”
Section: Discussionmentioning
confidence: 80%